Exposure characteristics and risk assessment of air particles in a Chinese hotel kitchen - Zanrong Zhou; Xiangjing Gao; Yiyao Cao; Hua Zou; Yulan Jin (Frontiers Media S.A., 2022)
BackgroundThe hazards of kitchen particles have attracted social attention, but their distribution characteristics and risk assessment are rarely reported.ObjectiveTo explore the temporal and spatial distribution characteristics of kitchen particles, analyze the variations in characteristics of number concentration (NC), mass concentration (MC), surface area concentration (SAC), and particle size distribution, provide reference indexes for evaluating worker exposure, evaluate the risk of kitchen particles, as well as suggest improvements and control measures.Patients and methodsDifferent cooking posts in a Chinese hotel kitchen were selected to monitor exposure to particles, explore the temporal and spatial distribution characteristics of NC, MC, and SAC of particles in the cooking post, analyze changes in the particle size, compare the individual exposure of particles between the cooking and steaming posts, and analyze the correlation between NC, MC, and SAC. Risk assessment of kitchen ultrafine particles was performed using a Nanotool.ResultsThe sizes and fluctuation ranges of NC10 − 500nm at cooking posts during lunch preparation and at peak periods were significantly higher than those at the end of the lunch period. The mean values of MC10 − 500nm during the lunch preparation peak and ending periods were 0.149, 0.229, and 0.151 mg m−3, respectively. The mean values of SAC10 − 500nm were 225, 961, and 466 μm2·cm−3, respectively. The mode diameter of exposed particles at the cooking post [(34.98 ± 2.33) nm] was higher than that at the steaming post [(30.11 ± 2.17) nm] (P < 0.01). The correlation between SAC10 − 500nm and NC10 − 500nm (r = 0.703) was the strongest. Nanotool gave a hazard rating ratio, exposure rating ratio, and risk ratio of 0.75.ConclusionThe sizes of the NC, MC, and SAC of the particles at the cooking post were related to the kitchen operations. Since kitchen particles are of high exposure and risk levels, protective measures should be formulated and implemented to deal with them safely.